A nurse-based intervention for improving medication adherence in cardiovascular patients: an evaluation of a randomized controlled trial - Sieben, Angelien (Patient Prefer Adherence, 2019)
Background: Poor medication adherence is a limitation in the secondary prevention of cardiovascular diseases (CVDs) and leads to increased morbidity, mortality, and costs. Purpose: To examine the process and effect of a nurse-led, web-based intervention based on behavioral change strategies to improve medication adherence in patients with CVD. Patients and methods: In this single-center, prospective, controlled clinical trial, cardiovascular patients were assigned to usual care, usual care plus a personalized website, or usual care plus a personalized website and personal consultations. Primary outcome was the level of adherence to cardiovascular medication. Data collection occurred between October 2011 and January 2015. Results: In total, 419 patients were randomized. Just 77 patients logged on the website and half of the invited patients attended the group consultation. Due to the limited use of the website, we combined the results of usual care and the usual care plus website group in one group (usual care) and compared these with the results of the group which received the nurse intervention (intervention group). No significant difference in adherence between the usual care group and the intervention group was observed. The adherence level in the usual care group was 93%, compared to 89% in the intervention group (p=0.08). 29% (usual care) and 31% (intervention group) of the patients showed a low adherence according to the Modified Morisky Scale® (p-value=0.94). The mean necessity concern differential was 3.8 with no differences between the two studied groups (mean 3.8 vs mean 3.9, p-value =0.86). Conclusion: Our intervention program did not show an effect. This could indicate that structured usual care provided to all cardiovascular patients already results in high medication adherence or that shortly after a cardiovascular event adherence is high. It could also indicate that the program did not have enough impact because there was not enough compliance with the intervention protocol. Trial registration: ID number NCT01449695, approved May 2011.